MOLECULAR DIAGNOSIS OF CRYPTOSPORIDIUM SSP. IN WATER BUFFALOES AT BABYLON PROVINCE, IRAQ - Al-Amery, A. R.; Al-Amery, A. M. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed recording the prevalence rates of the Cryptosporidium spp. and identify its species in buffalo at Babylon province by using microscopic (flotation and staining) and molecular technique to examined (100) buffalo fecal samples collected randomly from different sexes, ages, and regions, during the period from the beginning of October 2019, to end of March 2020. The percentage of infection with the Cryptosporidiosis was 40% by using the microscopic method, while, nested polymerase chain reaction (nPCR) technique showed the infection rate was 61%, and according to age groups, recorded higher infection 77.5% at (≤6) months age group, followed by age group (>6 -12) months and (>1 -2) years which showed 60% and 50%, besides, the age group (>2) years recorded 40%, which, the lowest infection rate. Also, females recorded (67.74%) as a higher prevalence rate than males (50%). Sequence analysis for ten samples that were positive by (n PCR) technique showed that 6 sequences belong to Cryptosporidium bovis (MT150692, MT150693, MT150694, MT150698, MT150699, and MT150701), while 3 sequence belongs to C. parvum (MT150696, MT150697, and MT150700), as well as, one of sequence belong to C. andersoni (MT150695), with a genetic difference of (0.010%) Datasets suggest strong genetic distinctiveness amongst species. The first diagnose of the Cryptosporidium and its species in water buffalo in Iraq by using molecular assay (nPCR).